Objective Measurement of Ball-Handling Proficiency in Wheelchair Sports: A Systematic Review - Altmann, Viola C.; Mason, Barry S.; Geurts, Tijmen; Camp, Sanne A. J. H. van de; Vanlandewijck, Yves C. (Frontiers in Rehabilitation Sciences, 2022)
Background: In Paralympic sports, classification of athletes based on the impact of impairments on the ability to perform is needed, to prevent a one sided and predictable outcome of the competition in which the least impaired athlete has the best chance to win. Classification is developing from expert opinion based to evidence based. In wheelchair court sports, there is evidence to support the impact of impairment on wheeled mobility, but not on ball handling. To assess the impact of impairment on the ability to perform ball handling activities, standardized tests for ball handling are needed. Purpose: To assess if reliable and valid standardised tests for the measurement of ball handling proficiency in wheelchair- or able bodied court sports exist; to assist in the development of Evidence Based Classification in wheelchair court sports according to the guidelines of the International Paralympic Committee. Methods: The review was conducted according to the Meta-Analysis of Observational Studies in Epidemiology statement. Search terms used were “wheelchair” and “ball” or “ball sports”, “test”, “performance”. Databases searched were Medline, Embase, PubMed and Sport Discus. Study quality was assessed using the Strengthening the Reporting of Observational studies in Epidemiology checklist. Results: Twenty-two articles were included. Foundational Movement Skills in ball handling proficiency were assessed. Tests for throwing maximal distance showed sufficient reliability and validity. Precision in throwing showed low to moderate reliability and conflicting results in validity. Throwing techniques differed between studies. Dribbling the ball showed high reliability, but conflicting results in validity. Conclusions: Tests for throwing maximal distance, throwing precision and dribbling the ball can be used in standardized tests for activity limitation in wheelchair court sports. However, tests need to be adapted and standardized and then reassessed for reliability and validity in athletes with and without arm impairment.